An Efficient DOA Algorithm for Phase Interferometers - Horng, Wei-Yau (IEEE transactions on aerospace and electronic systems, 2020)
The paper presents a comprehensible phase interferometer system which considers the four-element array as a cascade of two three-element subarrays and explores the mechanism how the short subarray resolves the ambiguity of the long subarray in a general manner. The resulted method can estimate the direction of arrival with high resolution while keeping very low ambiguity probability in the presence of noises over a wide field of view and a broadband with low computation complexity.